2018
DOI: 10.21873/invivo.11328
|View full text |Cite
|
Sign up to set email alerts
|

Successful Resection of a Non-functional Paraganglioma with Celiac Trunk Invasion Followed by Common Hepatic Artery Reimplantation – A Case Report and Literature Review

Abstract: Paragangliomas, as well as phaeochromocytomas, are vascular neuroendocrine lesions that might be encountered between neck and pelvis. In certain cases, a preoperative diagnosis is difficult to be established, so resection might be needed whenever a suspect mass is discovered at the imaging studies. Moreover, there are cases in which resection and reconstruction of an important vascular structure might be imposed. In this case report a 59-year-old patient was investigated for upper abdominal pain with postprand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Surgical resection represents the standard of care and can be performed traditionally by open surgery, while there has been a trend towards minimally invasive procedures in recent years [3,4]. Furthermore, as in our case, exact preoperative diagnosis may be impossible to be established and surgical excision of a suspicious mass may be needed [6]. Benefits of laparoscopy include better visualization and accuracy in dissection due to the optical magnification, reduced postoperative pain, earlier bowel mobilization, shorter length of hospitalization, and better cosmesis [3,15].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Surgical resection represents the standard of care and can be performed traditionally by open surgery, while there has been a trend towards minimally invasive procedures in recent years [3,4]. Furthermore, as in our case, exact preoperative diagnosis may be impossible to be established and surgical excision of a suspicious mass may be needed [6]. Benefits of laparoscopy include better visualization and accuracy in dissection due to the optical magnification, reduced postoperative pain, earlier bowel mobilization, shorter length of hospitalization, and better cosmesis [3,15].…”
Section: Discussionmentioning
confidence: 88%
“…Parasympathetic paragangliomas are usually inactive and located mostly in the neck and skull base, while sympathetic paragangliomas are mainly located in the retroperitoneum and usually produce and secrete norepinephrine [2,3]. Up to 15% of retroperitoneal paragangliomas are non-functional, and up to 10% are functional without clinical manifestation, although they resemble functional ones histologically and immunologically [4][5][6]. Their clinical presentation varies depending on their location, size, and secretion status, while their diagnosis and treatment may be challenging due to their close proximity to major vessels and surrounding organs, demanding multidisciplinary medical approach and cooperation [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, improvement in imaging, surgical techniques and postoperative management of patients with hepato-bilio-pancreatic malignancies have provided the possibility of performing successful surgical procedures with an increasing complexity (6-9). As a consequence, a significant number of cases which would have been otherwise considered as candidates for palliative treatment only are nowadays submitted to surgery with curative intent (10)(11)(12)(13). Despite the technological advances, it has been shown that up to 52% of patients who benefit from pancreatoduodenectomy also need vascular resection (4,5,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Bacalbasa et al . reported a case involving invasion of the celiac artery in which the paraganglioma and celiac artery were resected en bloc and the common hepatic artery was anastomosed to the abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the challenges of resection of paragangliomas. Bacalbasa et al 2 reported a case involving invasion of the celiac artery in which the paraganglioma and celiac artery were resected en bloc and the common hepatic artery was anastomosed to the abdominal aorta. Ogawa et al 3 described a paraganglioma arising on the back of Spiegel's lobe in a woman with kyphosis, and resection was performed by laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%